Elimination of Redundant Synaptic Inputs in the Absence of Synaptic Strengthening - Wang, Hao (Society for Neuroscience, 2011)
Synaptic refinement, a developmental process that consists of selective elimination and strengthening of immature synapses, is essential for the formation of precise neuronal circuits and proper brain function. At glutamatergic synapses in the brain, activity-dependent recruitment of AMPA receptors (AMPARs) is a key mechanism underlying the strengthening of immature synapses. Studies using receptor overexpression have shown that the recruitment of AMPARs is subunit specific. With the notable exception of hippocampal CA3–CA1 synapses, however, little is known about how native receptors behave or the roles of specific AMPAR subunits in synaptic refinement in vivo. Using patch-clamp recordings in acute slices, we examined developmental refinement of whisker relay (lemniscal) synapses in the thalamus in mice deficient of AMPAR subunits. Deletion of GluA3 or GluA4 caused significant reductions of synaptic AMPAR currents in thalamic neurons at P16–P17, with a greater reduction observed in GluA3-deficient mice. Deletions of both GluA3 and GluA4 abolished synaptic AMPAR responses in the majority of thalamic neurons, indicating that at thalamic relay synapses AMPARs are composed primarily of GluA3 and GluA4. Surprisingly, deletions of GluA3 or GluA4 or both had no effect on the elimination of relay inputs: the majority of thalamic neurons in these knock-out mice—as in wild-type mice—receive a single relay input. However, experience-dependent strengthening of thalamic relay synapses was impaired in GluA3 knock-out mice. Together these findings suggest that the elimination of immature glutamatergic synapses proceeds normally in the absence of synaptic strengthening, and highlight the role of GluA3-containing AMPARs in experience-dependent synaptic plasticity.